CITRA PEREMPUAN DALAM NOVEL SURGA YANG TAK DIRINDUKAN 2 KARYA ASMA NADIA - Anggreni, Lidhya; Effendy, Chairil; Wartiningsih, Agus (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe Image of Women in an Unwanted Heavenly. The method in this research is the reading method. The data source of the research was obtained from the Heavenly Unwanted novel 2 Asma Nadia's work published by Asma The first printed publishing house November 2016 with data in the form of words, phrases, clauses and sentences in SYTD2, which were grouped based on the form of the female image of the domestic and public domains of Arini and Mei Rose, the meaning of women's image, and the form of the implementation plan of the study results. Based on the results of data analysis, this study produced 12 forms of female image of the domestic realm of Arini figures, 7 manifestations of domestic realm images of Mei Rose. Also found is the form of the female image of the public domain of Arini's figure, 3 the form of the female image of the public domain of Mei Rose's figure. The results of research on the meaning in the SYTD2 novel found 2 forms of meaning. The results of the analysis produce RPP that can be implemented in Indonesian language class XII even semester 2013 curriculum in KD 3.3 Analyze history, news, advertising, editorial / opinion stories, and fiction stories in the novel both through oral and written and and Basic Competencies (KD): 4.2 Producing a novel text that is coherent according to the characteristics of the text both orally and in writing.Keywords:the image of women, the domestic realm, the public sphere, meaning